2002
DOI: 10.1073/pnas.062660699
|View full text |Cite
|
Sign up to set email alerts
|

Unidirectional rotary motion in a liquid crystalline environment: Color tuning by a molecular motor

Abstract: Life could not exist without motion induced by a variety of molecular motors. The construction of artificial motors by chemical synthesis, which can power motions that lead to macroscopic detectable effects in a system, is a major endeavor in contemporary science. To move toward this goal, a host-guest system, composed of a nematic liquid crystal film doped with a chiral light-driven molecular motor, is assembled. Irradiation of the film results in unidirectional rotary motion of the molecular motor, which ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
106
0
6

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 183 publications
(114 citation statements)
references
References 31 publications
2
106
0
6
Order By: Relevance
“…In fact, an internal, 360°rotation was induced in one specific direction (i.e., clockwise or counterclockwise) upon input of photons and thermal energy. On the road toward applications, it was shown that the phase of liquid crystals can be controlled when doped with small portions of optically enriched molecular motor, and micro objects can be moved (18)(19)(20). In addition, molecular motors were recently grafted on gold (21) and quartz surfaces (22).…”
mentioning
confidence: 99%
“…In fact, an internal, 360°rotation was induced in one specific direction (i.e., clockwise or counterclockwise) upon input of photons and thermal energy. On the road toward applications, it was shown that the phase of liquid crystals can be controlled when doped with small portions of optically enriched molecular motor, and micro objects can be moved (18)(19)(20). In addition, molecular motors were recently grafted on gold (21) and quartz surfaces (22).…”
mentioning
confidence: 99%
“…3A) could be added at ∼2-6 wt% in a liquid-crystal (LC) matrix and still undergo unidirectional rotary motion that induced color changes in the reorganized LC material (24). Improving on this feat, Feringa's group demonstrated in 2006 that a newly designed molecular motor 17 (Fig.…”
Section: +mentioning
confidence: 99%
“…Of particular interest to the study described here is the class of crystalline molecular machines, 14,15 which are rigid systems of individual functional molecules that can either interact with one another in a well-defined way, much like a conventional machine, or act collectively to affect the macroscopic properties of the bulk. Examples of the latter have already been demonstrated in the liquid crystal phase, where properties of the constituent molecules have been modified to react to external stimuli, changing bulk properties such as the color 16 or helicity. 17 The alternative approach of constructing systems of molecules that mimic macroscopic mechanical machines presents a significant challenge in crystal engineering, as welldefined multicomponent systems are needed in which the functions of the individual molecules can be correlated with one another.…”
Section: Introductionmentioning
confidence: 99%